Computerization of the Learning Process is the Main Problem of Our Modern Society - Makhmudova Nargiza Rakhmatullaevna (Zien Journals, 2023)
The level of possession of knowledge, or, more generally, information, begins to determine the political and economic status of states. And for successful work in such conditions, states need people - highly qualified specialists who meet the highest requirements of our time. Therefore, at the turn of the millennium, education turns into one of the most valuable strategic resources - human capital and knowledge, which ultimately determines the general level of development of society
Keywords: computerization of education; possession